Using Directive Speech Acts to Understand the Dialogue in a Short Film Script: A Case of Admit One - Jaganegara, Haidar (Sekolah Tinggi Bahasa Asing JIA, 2024)
Knowing speech acts is necessary for comprehending and understanding the meaning of character's dialogue, particularly in film script that employ performative language. Each character is responsible for understanding their lines, while the readers must grasp the overall context. The study, therefore, aims to analyse the kinds of directive speech acts in Admit One short film script. The paper applied the descriptive qualitative method, while the data were collected by closely observing the dialogues containing directive speech act both directly-indirectly and literal-non literal. The results showed in the data findings running ten types of directive speech acts in the data findings, such as command (11.36%), begging (4.55%), asking (43.18%), defending (6.81%), warning (2.27%), insisting (6.81%), suggesting (6.81%), ordering (11.36%), permitting (4.55%), and advising (2.27%). Later, this research is expected to provide profound insights to the reader about pragmatics study to analyse directive speech acts for further studies.